Approximate Solution of Linear Fuzzy Initial Value Problems Using Modified Variaional Iteration Method - S. Fadhel, Fadhel; M. Sagban, Hussein (Al-Nahrain Journal of Science, 2021)
The main objective of this paper is to solve fuzzy initial value problems, in which the fuzziness occurs in the initial conditions. The proposed approach, namely the modified variational iteration method, will be used to find the solution of fuzzy initial value problem approximately and to increase the rate of convergence of the variational iteration method. From the obtained results, as it is expected, the approximate results of the proposed method are more accurate than those results obtained without using the modified variational iteration method.